Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Kantor Pusat Pelatihan Kerja Daerah (PPKD) Jakarta Timur - Putri, Selviana Riski Rahma; Purnomo, Martinus Wahyu (Politeknik Negeri Ambon, 2024)
This study aims to determine the effect of leadership style and work environment on employee performance at the East Jakarta Regional Job Training Center (PPKD) Office both partially and simultaneously. This research uses a quantitative approach with associative methods. Data collection techniques using observation, questionnaires and literature studies. The number of samples in this study were 53 respondents and the data were processed using the SPSS.21 application. The results showed that leadership style partially had a positive and significant effect on employee performance, as evidenced by the T test obtained from the t value of 4,081> greater than t table 2,00856 and a significance value of 0,000 < smaller than 0,05. The work environment partially has a positive and significant effect on employee performance, as evidenced by the results of the T test obtained from the t value 3,364> greater than t table 2,00856 and a significance value of 0,001 < smaller than 0,05. Then the leadership style and work environment simultaneously have a positive and significant effect on employee performance. This is evidenced based on the results of the F test obtained from the calculated f value of 33,518> greater than f table 3,18 and a significance value of 0,000 < smaller than 0,05.